PERSPEKTIF PERANAN HUKUM DALAM PEMBANGUNAN EKONOMI TERHADAP PENYELESAIAN SENGKETA EKONOMI - Naufal Fadillah, Rozan; Ananda Oviana, Rurri; Manulang, Murdani; Ramdhani, Rizki; Santoso, Ichsan; Rafi Billah, Muhammad; Ruslina, Elli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study aims to determine the extent to which the role of law in economic development on the perspective of dispute resolution in the Commercial Court. The role of law in economic development, the role of law is very necessary and increasingly important, at least it can be used as a momentum to be able to display the law with its corrective role, correcting and improving the behavior of state officials, various policies and rules that underlie various policies in the economic field. In the legal process, namely the Formil Law in the form of examination procedures and limited legal remedies, approaching the acceleration of case settlement, as well as the Material Law very simply regulates the requirements for bankruptcy and PKPU statements in the Commercial Court.Keywords: Economic Dispute Resolution, Commercial Court